Prevenção e controle da COVID-19 em pacientes diabéticos mellitus tipo 2: percepção e práticas no cotidiano das orientações médico-científicas nos territórios de abrangência da atenção primária à saúde - SOUSA, Eline Maria Santos de (2022)
Introduction: COVID-19 is a acute respiratory syndrome,potentially serious, highly transmissible and globally distributed, which resulted in an overload on the health system worldwide, and revealed the existence of considerable differences in mortality from the infection. Advanced age and comorbidities such as diabetes mellitus have been associated with a bad prognosis. Objective: To analyze how type 2 diabetic patients perceive and manifest into everyday practices, at the individual, family and collective levels, the prevention and control measures of COVID-19. Methodology: a quantitative-qualitative, transversal research was used. The study was realized in territories covered by Primary Care Strategy (PCS) São Cristóvão Helth Center, São Luís – MA. The variables of interest were recorded in the first stage through a semi-structured online questionnaire with closed questions and in the second stage, a dialogued interview was applied. Results: The study sample consisted of patients aged 18 to 89 years, with a predominance of 40 to 59 years (48.7%), women (72%), married (35.2%), complete average study (33.9%), self-declared brown (85.4%), families with 1 to 3 components per house (60.9%), residences with 2 rooms (40.2%), piped water (95.1%) %), and only 1 bathroom (62.1%). In the qualitative analysis, the descendent hierarchical classification identified five classes which created four categories of qualitative analysis: (Covid-19 confrontation strategies; Challenges/fears experienced in the context of the pandemic; Credibility in information; and PCS performance in the pandemic period) and by similarity the tree of words presented the following ramifications: “Health”; “Being/Alone”; "People"; “Believe/Information”, “Stay/Home”; “Difficult/Distancing”. Conclusion: It is concluded that most of the interviewed recognized the severity of the pandemic, the importance of following the recommendations on protection measures and stated the credibility of the information received, especially by health and television professionals, we also observed that the fear of having the disease triggers negative feelings. It’s also concluded the dilemma which despite the participants give importance and credibility to preventive measures, they did not apply them totally because they had to go out to work and the believed in contamination in this sense. Final considerations: In this sense, studies of this nature within the scope of Primary Care can suggest importante tools to promote permanent education by the segments responsible for disseminating information in the communities in the face or new confrontations.